2015
DOI: 10.1007/s00894-015-2848-1
|View full text |Cite
|
Sign up to set email alerts
|

The antiradical activity of some selected flavones and flavonols. Experimental and quantum mechanical study

Abstract: The aim of the study was to examine the antiradical and antioxidant activity of some flavones and flavonols with different models of hydroxylation and methoxylation. Antiradical activity was measured using ABTS and DPPH radicals and ferric ions (FRAP test). The reduction potential of the compounds was also investigated by determination of minimal hydrogen abstraction energy for each of the hydroxyl hydrogens of all compounds using quantum chemistry methods. Quercetin appeared to be a strong antioxidant when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 55 publications
3
27
1
1
Order By: Relevance
“…This study also revealed that X. caffra had strong antiradical activities than most other plant materials reported in the literature. Several studies have reported the presence of higher antiradical activities in different tea species than other plant materials [34][35][36][37]. However the quantities reported are lower than those of X. caffra observed in this study.…”
Section: Antiradical Activitiescontrasting
confidence: 62%
“…This study also revealed that X. caffra had strong antiradical activities than most other plant materials reported in the literature. Several studies have reported the presence of higher antiradical activities in different tea species than other plant materials [34][35][36][37]. However the quantities reported are lower than those of X. caffra observed in this study.…”
Section: Antiradical Activitiescontrasting
confidence: 62%
“…Our research clearly showed that phloridzin antiradical activity is high (higher than rutin). Our earlier research [40] showed that the presence of a hydroxyl group situated at the 4′ position in the B ring is very important for antiradical activity of flavones and flavonols (see phloridzin in Figure 5). It seems that in addition to the structure of 2,4,6 trihydroxyacetophenone with a hydroxyl group bonded to aromatic ring A at position 2 in phloridzin [39], also the 4′ hydroxyl group present in the B ring may be important for antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Deviation of angles from the normal value 120°is due to the presence of hyperconjugative interaction. The torsion angles N-C(13)-C(12)-O (15) and N-C(9)-C(8)-O(11) with value −1.8°and −3.6°indicate that the glycinato arms are almost planar. To increase the strain in the glycinato arms they can be coordinated.…”
Section: Geometrical Optimizationmentioning
confidence: 99%
“…Dunning's basis set (aug-cc-pVDZ) has also been chosen apart from the regular basis set and implemented in various DFT methods. Computational techniques within the frameworks of DFT calculations and MD simulations provide outstanding tools for complementing experimental findings and understanding the reactivity of various molecular structures [14][15][16][17]. Various scientific and industrial areas rely on the efficiency of computational molecular modeling techniques [18][19][20][21][22].…”
mentioning
confidence: 99%